Development of static standing workstation design dimensions for Malaysian workers - Hassan, Siti Nuraini (2019)
A good workstation design must be comfortable, safe and easy to use for the workers. Unsuitable design of workstation may lead to musculoskeletal symptoms such as at the upper limbs, neck and lower back. Using the anthropometric dimensions of the workers, a better fit between the workers and the workstation design can be achieved. A total cost of RM13, 593,357.59 was paid by the Social Security Organization of Malaysia (SOCSO) compensation of musculoskeletal disorder for 537 cases within the last 5 years which are the highest cases claimed under the category of others occupational diseases. Although workstation design guideline is available and various standards are being referred to, there is a limited study on matching the anthropometric data of the Malaysian workers with the dimensions of the workstation in Malaysia. This study was carried out to identify the relevant anthropometric dimension for standing workstation, develop an ergonomics workstation standing dimension suitable for the Malaysian population and to validate anthropometric dimension for standing workstation design. Methodology of this study was by using questionnaire and a total of 1268 data was successfully collected with 30 anthropometric dimensions of Malaysian workers consist of 929 males and 329 females from 10 sectors of industries classified under Occupational Safety and Health Act 1994. The measurements based from the guidelines recommended by MS ISO 7250-1:2008, Basic Human Body Measurement for Technological Design using anthropometric grid and traditional measuring tools. Statistical Program for Social Science (SPSS) is used to analyse the data Descriptive statistics and T-test between male and female. CATIA V5 RULA Analysis and CATIA V5 Biomechanics Single Action Analysis are used to validate the recommended dimension. This study was carried out 17 anthropometry dimensions (standing measurement) from 30 anthropometry dimension, there is no significant difference found in the researcher measured data for 11 out of the 17 measurements. Four significant findings were recorded in this study namely, anthropometric dimensions for standing workstation design which are stature, standing eye height, standing elbow height and fingertip reach. It also highlighted that the best dimension are overhead clearance more than 183.4cm, working height range of adjustable from 93.4cm to 115.9cm, Visual Display Terminal (VDT) height adjustable range from 148.9cm to 157.6cm and maximum reach with 73.5cm. Findings of this study has granted imperative information in designing standing workstation for Malaysia industry to help in creating a safer, healthier and comfortable workplace.